MOLECULAR MECHANISM FOR SEPTORIA AVENAE DISEASE RESISTANCE IN AVENA SATIVA L. (OAT)-A CRITICAL REVIEW - Ali Hasnian; Zahid Mehmood; Naveed Anjum; Muhammad Umar Farooq Awan (Journal of Animal and Plant Sciences, 2026)
Avena sativa L. (oat) is a cereal crop usually cultivated globally after wheat, rice maize, and barley. In recent years, its cultivation has been affected by the Septoria avenae f. sp. avenae fungus, which is frequently known as septoria leaf blotch disease. This review article examines the published data of the genomic study of septoria leaf blotch disease resistance in oats. There are many resistance QTLs/genes have been acknowledged within the gene pool oat against Septoria avenae. Weedy and wild species of Avena harbour precise genes that provide resistance to septoria leaf blotch with discoveries made across in 12 wild oat species. Disrupting avenacinase biosynthesis may halt the spread of septoria leaf blotch. The purpose of crossbreeding resistant wild species with cultivated oats (Avena sativa L.) is to find the resistance genes. The transfer of resistance genes from weedy Avena strigosa and wild oat’s species (Avena sterilis, Avena macrostachya, and Avena fatua) into high-yielding oat varieties is also ongoing. There are some new sequencing techniques, including genomic selection (GS), quantitative trait loci (QTL) mapping, marker-assisted-selection (MAS), and genome-wide association studies (GWAS), and CRISPR/Cas9, are progressive techniques and genome editing that help to find genomic regions associated to Septoria avenae resistance in oats and other breeding traits. The advancement of modern genotyping for disease resistance, advanced technologies for sequencing, development in bioinformatics and complete genome sequencing, breeding septoria disease resistance in oats is becoming gradually attainable.
Keywords: Avena sativa L.; Septoria avenae; Avenacinase; Wild oat; QTLs; Sequencing Techniques